Challenges in the transition from resident to attending physician in general internal medicine: a multicenter qualitative study - Christine Roten; Christine Baumgartner; Stefanie Mosimann; Yonas Martin; Jacques Donzé; Felix Nohl; Simone Kraehenmann; Matteo Monti; Martin Perrig; Christoph Berendonk (BMC Medical Education, 2022)
Abstract Background The attending physician in general internal medicine (GIM) guarantees comprehensive care for persons with complex and/or multiple diseases. Attendings from other medical specialties often report that transitioning from resident to attending is burdensome and stressful. We set out to identify the specific challenges of newly appointed attendings in GIM and identify measures that help residents better prepare to meet these challenges. Methods We explored the perceptions of 35 residents, attendings, and department heads in GIM through focus group discussions and semi-structured interviews. We took a thematic approach to qualitatively analyze this data. Results Our analysis revealed four key challenges: 1) Embracing a holistic, patient centered perspective in a multidisciplinary environment; 2) Decision making under conditions of uncertainty; 3) Balancing the need for patient safety with the need to foster a learning environment for residents; and 4) Taking on a leader’s role and orchestrating an interprofessional team of health care professionals. Newly appointed attendings required extensive practical experience to adapt to their new roles. Most attendings did not receive regular, structured, professional coaching during their transition, but those who did found it very helpful. Conclusions Newly appointed attending physician in GIM face a number of critical challenges that are in part specific to the field of GIM. Further studies should investigate whether the availability of a mentor as well as conscious assignment of a series of increasingly complex tasks during residency by clinical supervisors will facilitate the transition from resident to attending.